2018
DOI: 10.1016/j.rboe.2017.08.021
|View full text |Cite
|
Sign up to set email alerts
|

Effect of surgical treatment on the quality of life in patients with non-traumatic avascular necrosis of the femoral head

Abstract: ObjectiveAvascular necrosis of the hip is a common debilitating disease during the fourth and fifth decades of life. This study attempted to evaluate quality of life in patients with avascular necrosis of the hip joint before and after surgery.MethodsIn this study, 40 patients with avascular necrosis of the hip who underwent total hip arthroplasty, bipolar surgery, or cord compression were examined during 2006–2013. Harris Hip Score was used to assess the hip joint function and quality of life before and after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…In the pre-collapse stage, the primary treatment is hip preservation, consisting of conservative treatment or core decompression, whereas in a post-collapse state, the standard treatment is total hip arthroplasty (THA) (8). Mohammad et al reported that THA improved quality of life in patients with post-collapse non-traumatic ONFH (9). However, in our institute, some patients in the postcollapse state denied having an operation and considered continuing conservative treatment.…”
Section: Introductionmentioning
confidence: 79%
“…In the pre-collapse stage, the primary treatment is hip preservation, consisting of conservative treatment or core decompression, whereas in a post-collapse state, the standard treatment is total hip arthroplasty (THA) (8). Mohammad et al reported that THA improved quality of life in patients with post-collapse non-traumatic ONFH (9). However, in our institute, some patients in the postcollapse state denied having an operation and considered continuing conservative treatment.…”
Section: Introductionmentioning
confidence: 79%
“…29 AVN is a major cause of poor quality of life which may improve markedly after surgery. 30 To improve overall health and satisfaction in life in our patients with SLE, AVN must be addressed early and thoroughly by screening, monitoring, and adequate management.…”
Section: Discussionmentioning
confidence: 99%
“…[ 11 18 ] These options include medications, surgical treatments, and other alternative interventions, such as Chinese herbal medicine, acupuncture, rest, extracorporeal shock wave therapy, and electrical stimulation. [ 11 18 ] However, these options still suffer from limited efficacy, and even very server adverse events (AEs) and complications. Thus, alternative candidates with few AEs are urgently needed to treat this condition.…”
Section: Introductionmentioning
confidence: 99%